Analysis Study on Scaling Up Production of Lithium-Ion Batteries (LIB) Cathode Material at National Battery Research Institute - R. Adji Fatahillah Ramdhan; Hieronimus Matthew Ekaristianto; Yohanes Darryl Goenawan; Moh. Wahyu Syafi'ul Mubarok; Muhammad Fakhrudin; Evvy Kartini; Alan J. Drew (NBRI Press, 2023)
Innovation for energy storage becomes essential for advancing the electrification goal. Over the past ten years, the trend toward electric vehicles and renewable energy has placed an unexpectedly high demand on battery technology. The development of lithium-ion batteries (LIB) has been touted as a revolution in energy storage technology. Due to its promising performance, LIB has not only performed well for electronic applications but is also well-known for its scalability for mass production. Although it is projected that LIB will continue to dominate the market for the succeeding ten years, the rise of battery giga-factories is still sluggish. The biggest barrier to increasing end-to-end battery production on an industrial scale is the complexity of the manufacturing process and the number of machines used. Because the viability of the firm may be impacted by inaccurate calculations regarding the battery production chain. Investigating how to increase battery cathode production from a laboratory to an industrial scale is therefore important. National Battery Research Institute, one of Indonesia's top battery research centers, contributed as the study's subject. The calculation was focused on NMC 811 cathode active material by considering cost structure factor such as raw materials, machinery, power consumption, and manpower. The result has successfully estimated the total cost for scaling-up 100 Kg production of NMC 811 cathode per batch or 36 Tons in a year. As a note, the data that was discussed in this manuscript limited on machinery, power consumption, and manpower aspect. While raw material cost will be discussed in detail, separately in another article.